The use of dermoscopy to support the diagnosis of sarcoptic mange in two dogs. Issue 3 (20th February 2022) - Legnani, Sara; Buckley, Laura
Abstract : Two unrelated adult dogs presenting with chronic pruritic dermatitis were diagnosed with sarcoptic mange through the in vivo dermoscopic visualisation of Sarcoptes scabiei mites. The species of mite was confirmed via microscopy of superficial skin scrapings taken from lesional skin. Dermoscopy offers rapid point‐of‐care, noninvasive screening for dogs with sarcoptic mange. Abstract : Two unrelated adult dogs presenting with chronic pruritic dermatitis were diagnosed with sarcoptic mange through the in vivo dermoscopic visualisation of Sarcoptes scabiei mites. The species of mite was confirmed via microscopy of superficial skin scrapings taken from lesional skin. Dermoscopy offers rapid point‐of‐care, noninvasive screening for dogs with sarcoptic mange. 摘要: 通过疥螨的体内皮肤镜可视化, 2只无关成年犬表现为慢性瘙痒性皮炎, 最终被诊断为疥螨病。通过浅刮皮肤从病变处采集样本进行显微镜检查, 确认螨虫种类。皮肤镜为疥螨病犬提供了快速的即时、非侵入性筛查。 Résumé: Deux chiens adultes non apparentés présentant une dermatite prurigineuse chronique ont été diagnostiqués avec une gale sarcoptique par la visualisation dermoscopique in vivo d'acariens Sarcoptes scabiei . L'espèce d'acarien a été confirmée par microscopie de raclages cutanés superficiels prélevés sur la peau lésionnelle. La dermoscopie offre un dépistage rapide et non invasif au chevet du patient pour les chiens atteints de gale sarcoptique. Zusammenfassung: Zwei nicht verwandte Hunde, die mit chronischer juckender Dermatitis vorgestellt wurden, wurden mittels in vivo dermoskopischer Visualisierung von Sarcoptes scabiei Milben mit Sarkoptesräude diagnostiziert. Die Milbenspezies wurde mittels Mikroskopie von oberflächlichen Hautgeschabseln, die von veränderter Haut genommen wurden, bestätigt. Die Dermoskopie bietet eine rasche Point‐of‐care, nicht invasive Screening Methode bei Hunden mit Sarkoptesräude. 要約: 慢性掻痒性皮膚炎を呈した血縁関係のない成犬2頭を、疥癬虫をin vivoにおけるダーマスコープにより視覚化し、疥癬と診断した。また, 病変部皮膚から採取した表在性皮膚スクレーピングの顕微鏡観察により、ダニの種類を確認することができた。ダーモスコピーは、疥癬の犬における迅速な診療現場での、非侵襲的なスクリーニングを提供する。 Resumo: Dois cães adultos apresentando dermatite pruriginosa crônica foram diagnosticados com sarna sarcóptica através da visualização dermatoscópica in vivo dos ácaros Sarcoptes scabiei . A espécie de ácaro foi confirmada por avaliação microscópica de raspados cutâneos superficiais coletados de pele lesional. A dermatoscopia é um método diagnóstico que oferece triagem ambulatorial rápida e não invasiva para cães com sarna sarcóptica. Resumen: Dos perros adultos no relacionados que presentaban dermatitis pruriginosa crónica fueron diagnosticados con sarna sarcóptica a través de la visualización dermatoscópica in vivo de los ácaros Sarcoptes scabiei . La especie de ácaro se confirmó mediante microscopía de raspados cutáneos superficiales tomados de la piel lesionada. La dermatoscopia ofrece una detección rápida y no invasiva en el punto de atención primaria para perros con sarna sarcóptica.